Chronic obstructive pulmonary disease in China: the potential role of indacaterol - Gao, Jinming; Prasad, Niyati (Journal of Thoracic Disease, 2013)
Chronic obstructive pulmonary disease (COPD) is becoming a leading cause of morbidity and mortality in China, with tobacco smoking, biomass fuel use and genetic susceptibility being the major risk factors. COPD poses a high economic burden with the total expenditure per patient costing 40% and nearly one-third of an average family income in urban and rural areas of China, respectively. Despite the use of the Global Initiative for Chronic Obstructive Lung Disease strategy document being recommended for the diagnosis and management of COPD, the majority of patients with COPD go undiagnosed or are not managed appropriately by physicians. Long-acting β2-agonists (LABAs) have long been used for symptomatic management of COPD, with salmeterol and formoterol being the commonly used twice-daily treatments. Indacaterol is the first once-daily LABA, approved at a dose of 150 μg once daily in China. Several phase III studies have shown that indacaterol 150 μg improves lung function, breathlessness, health status, exacerbations, rescue medication use and symptoms, as compared with placebo and other bronchodilators, in patients with COPD, with a rapid onset of action following first dose and a good safety and tolerability profile. In this review we elaborate on the efficacy and safety results from several such studies.